Modeling and Control of a Nonlinear Active Suspension Using Multi-Body Dynamics System Software (Jurnal Teknologi (Sciences & Engineering), 2014)
This paper describes the mathematical modeling and control of a nonlinear active suspension system for ride comfort and road handling performance by using multi-body dynamics software so-called CarSim. For ride quality and road handling tests the integration between MATLAB/Simulink and multi-body dynamics system software is proposed. The control algorithm called the Conventional Composite Nonlinear Feedback (CCNF) control was introduced to achieve the best transient response that can reduce to overshoot on the sprung mass and angular of control arm of MacPherson active suspension system. The numerical experimental results show the control performance of CCNF comparing with Linear Quadratic Regulator (LQR) and passive system.Â